Vesicular storage, vesicle trafficking, and secretion of leptin and resistin : the similarities, differences and interplays - Ye, Feng (2012)
Adipose tissue is a highly active endocrine organ secreting a variety of signaling molecules called adipokines. Leptin and resistin are two adipokines critically involved in metabolic homeostasis. Nevertheless, the secretory pathways of these adipokines and their interplays are poorly elucidated. In this work, we have comparatively studied several key aspects of leptin and resistin secretion from 3T3-L1 adipocytes. It was found that leptin and resistin molecules are compartmentalized into different secretory vesicles. The trafficking of leptin and resistin vesicles, and the secretion of leptin and resistin are oppositely regulated by insulin/glycolytic substrates and cAMP/protein kinase A. Interestingly, these two adipokines adversely influence each other on secretion and vesicle trafficking. Finally, we demonstrated that both leptin and resistin secretion are Ca2+ dependent.